IMPLEMENTATION OF SCHOOL LITERACY MOVEMENT TO ENHANCE READING INTEREST OF STUDENTS IN SOUTH SUMATRA - Hamzah, Amir; Tasya, Wilda; Rusdi, Amir; Krisetyaningsih, Krisetyaningsih; Tastin, Tastin (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2023)
This research aimed to evaluate the implementation of the School Literacy Movement (SLM) program, identifying the supporting and hindering factors to enhance the reading interest of students in some Elementary Schools (ES) such as ES of Yayasan IBA in Palembang, Elementary Schools of  01 Indralaya in Ogan Ilir Regency, and Elementary Schools of 3 Kayu Agung in Ogan Komering Ilir Regency. The analysis used a qualitative method with a descriptive and multi-site approach using interview guidelines, questionnaires, and observation sheets as instruments. The results showed that the implementation of the SLM program in ES of 01 Indralaya and ES of 3 Kayu Agung, effectively fostered the reading interest of fourth-grade students according to the indicators published by the Ministry of Education and Culture, including the stages of habituation, development, and learning. The supporting factors of the program that were identified included Libraries, Reading Corners, Bulletin Boards, Reading Gardens and School Literacy Carts, Identity Boards Literacy Trees, Media Utilization, School Gardens, Public Engagement, SLM Team, School Gardens, Training and Study Tours, Reading Materials, and Reading Campaign Posters. Furthermore, the hindering factors were reluctance to study, a lack of reading habits, inability to read proficiently, and insufficient support for library management by qualified librarians.